2022
DOI: 10.1177/15500594221076347
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state EEG, Substance use and Abstinence After Chronic use: A Systematic Review

Abstract: Resting-state EEG reflects intrinsic brain activity and its alteration represents changes in cognition that are related to neuropathology. Thereby, it provides a way of revealing the neurocognitive mechanisms underpinning chronic substance use. In addition, it is documented that some neurocognitive functions can recover following sustained abstinence. We present a systematic review to synthesize how chronic substance use is associated with resting-state EEG alterations and whether these spontaneously recover f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 104 publications
3
22
0
Order By: Relevance
“…Based on these neurobiological changes, pharmacological targeting [47] and brain stimulation [48] have been suggested as plausible treatments for reversing the impacts of addiction on the brain. To date, however, previous studies focused on either the impacts of brief abstinence or that of acute nicotine consumption [49], and it still has not been directly examined whether the neural hints of individuals’ smoking history in the brain ever disappear even after a long period of successful abstinence. The current study addresses this gap by including past-smokers who smoked for at least six months and stayed abstinent for longer than 20 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these neurobiological changes, pharmacological targeting [47] and brain stimulation [48] have been suggested as plausible treatments for reversing the impacts of addiction on the brain. To date, however, previous studies focused on either the impacts of brief abstinence or that of acute nicotine consumption [49], and it still has not been directly examined whether the neural hints of individuals’ smoking history in the brain ever disappear even after a long period of successful abstinence. The current study addresses this gap by including past-smokers who smoked for at least six months and stayed abstinent for longer than 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known about the impacts of smoking on EEG coherence [49]. One previous study, while the sample size was small, reported a consistent pattern in alpha coherence, such that smokers showed higher coherence than age-matched non-smokers [55].…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalography (EEG) is a neurophysiological technique for measuring brain activity, and although much is known about EEG activity in acute (Fairbairn et al, 2021 ) and chronic (Hamidovic and Wang, 2019 ; Liu et al, 2022 ) substance use, knowledge regarding EEG activity in relation to longitudinal abstinence and treatment outcomes is sparse (Houston and Schlienz, 2018 ; Stewart et al, 2019b ; Jurado-Barba et al, 2020 ). However, building on over half a century of concentrated EEG research, there is a growing interest in applying EEG approaches for SUD treatment research.…”
Section: Introductionmentioning
confidence: 99%
“…However, building on over half a century of concentrated EEG research, there is a growing interest in applying EEG approaches for SUD treatment research. Metrics derived from EEG have good test-retest reliability (Tenke et al, 2017 ; Ip et al, 2018 ; Malcolm et al, 2019 ; Roach et al, 2019 ; Vázquez-Marrufo et al, 2020 ; Cofresí et al, 2022 ), are highly heritable (Van Beijsterveldt and Van Baal, 2002 ; de Geus, 2010 ; Gilmore et al, 2010 ) and widely used in SUD (Parvaz et al, 2011 ; Almeida-Antunes et al, 2021 ; Zhang et al, 2021b ; Liu et al, 2022 ), depression (de Aguiar Neto and Rosa, 2019 ), schizophrenia (Perrottelli et al, 2021 ), psychosis (Wang et al, 2022 ), neurodegeneration (Horvath et al, 2018 ), and pain (Ploner and May, 2018 ) research. High-quality EEG provides direct and millisecond-level access to regional and global neural activity (Sadaghiani et al, 2022 ), and indexes oscillatory communication (i.e., connectivity) within and between networks (Sadaghiani et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation